Application of Google Sites-Based Learning Media as Alternative Learning Media in Chemistry Education Learning - Herdini, Herdini; Linda, Roza; Wulandari, Putri Adita; Karimah, Annisatul; Nursiwan, Wimbi Apriwanda (Yayasan Keluarga Guru Mandiri, 2025)
The need for post-pandemic alternative media development in chemistry learning at school is the goal of this research. This study uses a research and development model. Alternative learning media developed in the form of website-based learning using Google Sites. Two media experts validated the material content, and the media content was validated by two additional media experts. Validation was carried out twice. The results of media validation in this study included the substance of media content, learning design, visual communication, and the use of software by media validators, with percentages of 98.44%, 98.75%, 93.75%, and 97.92%, respectively. The average score of 97.21% falls within the valid category. The results of material validation, based on aspects of content feasibility, pedagogical aspects, language assessment, and graphics, by the material validator, namely 95.83%, 95.83%, 100%, and 100%, with an average score of 97.91%, are included in the valid category. The trial was carried out at MA Hidayatul Marifah with 20 students. The results of teacher and student responses, respectively, were 92.17% and 90.12%, which were included in the good category.